Violence and the Sikhs - Mandair, Arvind-Pal ca. 20./21. Jh. (Cambridge elements. Elements in religion and violence, 2022)
Violence and the Sikhs interrogates conventional typologies of violence and non-violence in Sikhism by rethinking the dominant narrative of Sikhism as a deviation from the ostensibly original pacifist-religious intentions and practices of its founders. This Element highlights competing logics of violence drawn from primary sources of Sikh literature, thereby complicating our understanding of the relationship between spirituality and violence, connecting it to issues of sovereignty and the relationship between Sikhism and the State during the five centuries of its history. By cultivating a non-oppositional understanding of violence and spirituality, this Element provides an innovative method for interpreting events of 'religious violence'. In doing so it provides a novel perspective on familiar themes such as martyrdom, Martial Race theory, warfare and (post)colonial conflicts in the Sikh context.